PEOPLE’S PERSEPTION ABOUT EARLY MARRIAGE (A CASE STUDY IN DESA SUNGAI KUNING KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI) - Ade Maspupah; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in Desa Sungai Kuning  Kecamatan  SingingiKabupaten  Kuantan  Singingi. The purpose of this research is to find out the early marriage factors and what is people’s perception about  it. This research entitled “people’s perception about early marriage (aacase study in Desa Sungai Kuning  Kecamatan  Singing  iKabupaten  Kuantan  Singingi)”.  The focus topic of this research is what factors cause the early marriage and what are people’s perception about it. Subject of this research is KepalaDesa, SekretarisDesa, Religion figure, Ketua RT, Imam masjid, and respected people in Sungai Kuning. Sampling was done by purposive technique. Subject was contain of 6 people. Writer used qualitative descriptive method and data are analysed qualitatively. Data instruments are observation and interview. Result shows that the dominant factors of early marriage  are internal factor (the actors wants to marry) and external factors; economic and social factors (ex: unwanted pregnancy before marriage). The dominant perception is from the religion point of view, that religion says it is good to marry early to avoid any sexual activity outside marriage. From social point of view, people think that teenagers today have relationship outside out permitted norms. From economic point of view, people think that marriage will solve economic problems. Key word: people’s perception, teenagers, early marriage